Kajian Pengendalian Dampak Lingkungan Aktivitas Pembangunan Tower SUTET Dan GITET Oleh Perusahaan Ketenagalistrikan Daerah Jawa Timur - Perangin Angin, Regina Grasia; Rizka Novembrianto (Jurnal Serambi Engineering, 2025)
Electricity companies build substation towers to provide electricity to all parts of Indonesia. It is imperative to conduct environmental impact analysis on the construction of Extra High Voltage Overhead Line (SUTET) towers and Extra High Voltage Substations (GITET) because these projects have the potential to cause various negative impacts on the environment and surrounding communities. The impacts that may be generated are solid, liquid and B3 waste, decreased groundwater quality, noise, decreased ambient air quality, public health, and road damage. This study will obtain the results of the environmental and socio-economic impact analysis as well as mitigation methods to minimize the impacts that occur during construction, in accordance with applicable regulations. The research method used is a descriptive approach. Environmental protection policies are crucial in electricity development to support sustainable and environmentally friendly growth. Electricity companies are committed to biodiversity conservation and land restoration. They are committed to reducing negative impacts through sustainable practices.